MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DENGAN MENERAPKAN METODE VAK (VISUAL, AUDITORI, KINESTETIK) PADA SISWA KELAS I SDN 3 PEMENANG TIMUR - Rahayu, Fitriani; Mahendra, Juandra Prisma (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2022)
This study aims to determine the improvement of initial reading skills through the Visual, Auditory, Kinesthetic (VAK) method in 1st grade students at SDN 3 Pemenang Timur. This research is an effort to improve initial reading skills through the Visual, Auditory, Kinesthetic (VAK) method in grade 1 students at SDN 3 Pemenang Timur. This research was conducted with 2 cycles, each of which has 4 stages, namely planning, implementation, observation, and reflection. The subjects of the study were 1st grade students at SDN 3 Pemenang Timur with a total of 30 students. Data collection techniques was carried using observation sheets and reading tests. Based on the analysis of test results and observations, it was concluded that there was an increase in students' initial reading ability in each cycle. The average value result at the precyclical was 70.4 with a classical completion percentage of 47%. In the first cycle, the average value became 74.4 with a classical completion percentage of 67%. In cycle II, it increased again with an average value of 77.9 with a classical completion percentage of 83%. Thus, the VAK method can improve the initial reading skills in the first grade of SDN 3 Pemenang Timur.